2022
DOI: 10.1108/jet-12-2021-0068
|View full text |Cite
|
Sign up to set email alerts
|

The application of augmented reality in the learning of autistic students: a systematic and thematic review in 1996–2020

Abstract: PurposeMore and more diversity is present in our classrooms. As teachers, we must be able to respond to the different levels of learning presented by our students. Therefore, it is necessary to use the new emerging technologies as elements of response. Thus, the purpose of this paper is to develop a systematic and thematic review of the application of augmented reality (AR) in the learning of autistic students in the educational setting during the period 1996–2020 using the Web of Science and Scopus databases.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 90 publications
(261 reference statements)
0
2
0
1
Order By: Relevance
“…Lorenzo et al [21] applied the Web of Science and Scopus databases to develop a comprehensive review of how augmented reality (AR) helped autistic students in learning from 1996 to 2020, which set the foundation for designing an action protocol of AR activities for autistic students. In addition, Cheng et al [22] concluded that the AR educational program could improve students' knowledge and thinking ability.…”
Section: Augmented Reality (Ar) In Educationmentioning
confidence: 99%
“…Lorenzo et al [21] applied the Web of Science and Scopus databases to develop a comprehensive review of how augmented reality (AR) helped autistic students in learning from 1996 to 2020, which set the foundation for designing an action protocol of AR activities for autistic students. In addition, Cheng et al [22] concluded that the AR educational program could improve students' knowledge and thinking ability.…”
Section: Augmented Reality (Ar) In Educationmentioning
confidence: 99%
“…Augmented Reality is a technology that is increasingly being used in Education (Hanid et al, 2020;Hedenqvist et al, 2021;Medina & Ferrer, 2022). Augmented Reality can be used in learning, increasing the effectiveness of classroom teaching and mobile learning (Garrett et al, 2015;Li & Liu, 2022;Lorenzo et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Augmented Reality adalah teknologi yang semakin banyak digunakan dalam Pendidikan (Hanid, Said, & Yahaya, 2020;Hedenqvist, Romero, & Vinuesa, 2021;Medina & Ferrer, 2022). Augmented Reality bisa digunakan kedalam pembelajaran yang dapat meningkatkan efektifitas pengajaran dikelas dan pembelajaran mobile (Garrett, Jackson, & Wilson, 2015;Li & Liu, 2022;Lorenzo, Gilabert Cerdá, Lorenzo-Lledó, & Lledó, 2022).…”
unclassified